(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the structure, function, semantic properties and application aspects of the means of expressing the meaning of respect in the Uzbek language. The meaning of respect is a socio-positive subjective meaning with linguistic and speech means.